Application of higher order statistics to conformation radiotherapy treatment planning program - Tan, Boon Tiong. (2008)
1) We propose a steady-state Kalman filter-type recursive algorithm to determine intensity-modulated beams that yields an optimized dose distribution.2) We also propose a hybrid optimization approach, which combines the two algorithms to reach a global optimization solution in reasonable computation time.